A Study Of Landfill Leachate Treatment By Pacl, Sago Starch And Tapioca Starches, Hymenocallis Liriosme And Aloe Vera As Coagulants - Ong, See Leng (2010)
The properties and mechanism of reaction of tapioca starch, sago starch, Hymenocallis liriosme and Aloe vera potential in landfill leachate treatment has not yet been fully discovered and examined. Thus this study aims to determine the optimum dosage of PACl, tapioca starch, sago starch, Hymenocallis liriosme, Aloe vera and pH in the removal of COD, NH4-N, colour and SS for treating landfill leachate. Zeta potential for each coagulant used is measured and the capability of sago starch, tapioca starch, Hymenocallis liriosme and Aloe vera act as coagulant aids in reduce the dosage of PACl as coagulant is estimated. The sample of leachate is taken from PBLS. Four main parameters were studied including suspended solid, colour, chemical oxygen demand (COD), and ammoniacal nitrogen (NH4-N). Determination of zeta potential also was done for raw sample, and after coagulation using PACl and other four types of natural coagulants. Results indicated that the optimum dosage for PACl in landfill leachate treatment is 7200mg/L at pH 7.5. The dosage of PACl successfully reduce up to 62.5% in the assisted of sago starch as coagulant aid. While for tapioca starch, it reduces the PACl dosage up to 40%. For the green plants, Hymenocallis liriosme and Aloe vera, they show the capability in reduce the PACl usage up to 75% respectively. Among these natural coagulants, Hymenocallis liriosme and Aloe vera show highest capability as coagulant aids in reduce the dosage for PACl as coagulant. Composition and the structural of Hymenocallis liriosme and Aloe vera need for further investigation to obtain the higher pollutant removal efficiency. More quantitative research is necessary to get a better result for this study. Further research focused on the quantitative aspects of the coagulants studied would provide comparative data and more reliable results.